Fragility curves development for single span slab bridges: A case study for Peshawar Pakistan - Shafiq, Omair; Saffuan, Wan Ahmad; Ali, Syed Muhammad; Waqas, Muhammad; Khattak, Ghufranullah; Muhammad Aimran Amzar, Kamarudin (Semarak Ilmu Publishing, 2025)
Bridges play a critical role in a country's transportation network and assessing their vulnerability to seismic events is essential for effective risk management. This study focuses on the vulnerability assessment of single span slab bridges in Peshawar, Pakistan, located in seismic zone 2B, through nonlinear dynamic time history analysis using Incremental Dynamic Analysis Technique. Fragility curves are developed, considering ultimate limit states such as pounding between the slab and backwall, leading to backwall failure and subsequent backfill passive pressure failure. Themethodology encompasses model generation, loading analysis and fragility curve derivation. Empirical data collected from inventory surveys and theoretical modellingin CSi Bridge software inform model generation, while loading analysis incorporates acceleration time history plots from actual records and artificially generated spectra. Fragility curves are derived using MATLAB from capacity curves generated through Incremental Dynamic Analysis. Results indicate that single span slab bridges in Peshawar can withstand seismic loading requirements corresponding to a return period of 2475 years. The study aims to assist policymakers in prioritizing maintenance and allocating resources effectively to enhance infrastructure resilience. Furthermore, a simplified conclusion underscores the importance of ongoing maintenance and risk mitigation efforts for ensuring long-term infrastructure sustainability and community safety in earthquake-prone regions.